Pengaruh Kompres Air Jahe terhadap Penurunan Dismenorea Primer pada Remaja - napu, Lia afriani; Yusrah Taqiyah; Wa Ode Sri Asnaniar (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
Dysmenorrhea is a painful condition that occurs during menstruation that can interfere with activities and can cause pain in the lower abdomen, which radiates to the lower back and legs. Handling of dysmenorrhea can be done non-pharmacologically, one of which is ginger water compress therapy. The purpose of this study was to determine the effect of ginger water compresses on reducing dysmenorrhea pain in adolescents in SMA Negeri 5 Makassar. This research is a quantitative study with a quasi-experimental design and a one group pretest-posttest design which was conducted on 35 dysmenorrhoea students. The sampling technique used was purposive random sampling with a total sampling method that had been adjusted to the inclusion criteria and exclusion criteria. Bivariate analysis used the Wilcoxon test with a significance level of < 0.05. The results of this study indicate, before giving ginger water compress therapy to dysmenorrheal students there was mild, moderate, severe and very severe dysmenorrhoea. pretest-posttest on systolic-diastolic p Value = 0.000 and diastolic p Value = 0.000. The conclusion of this study is that there is an effect of giving ginger water compress soak therapy on dysmenorrhea in adolescent girls at SMAN 5 Makssar. Therefore, ginger water compress can be used as a non-pharmacological therapy that can be done independently to reduce dysmenorrhea pain.